2012
DOI: 10.1073/pnas.1205132109
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated STAT3 is crucial for methylation of tumor-suppressor gene promoters and inhibition by resveratrol results in demethylation

Abstract: The mechanisms underlying hypermethylation of tumor-suppressor gene promoters in cancer is not well understood. Here, we report that lysine acetylation of the oncogenic transcription factor STAT3 is elevated in tumors. We also show that genetically altering STAT3 at Lys685 reduces tumor growth, which is accompanied by demethylation and reactivation of several tumor-suppressor genes. Moreover, mutating STAT3 at Lys685 disrupts DNA methyltransferase 1-STAT3 interactions in cultured tumor cells and in tumors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(211 citation statements)
references
References 40 publications
(64 reference statements)
6
203
2
Order By: Relevance
“…5), thus providing new information on how U-STAT3 may contribute to the development of cardiac hypertrophy following angiotensin II stimulation. Additional Therapeutic Implications-Lee et al (25) reported that, by reducing STAT3 acetylation, ER␣ gene expression can be reactivated in tumors in which the ER␣ promoter had previously been methylated. Moreover, because inactivation of the ER␣ gene by DNA methylation strongly correlates with poor prognosis as well as an aggressive phenotype in cancers such as melanoma and the basal subtype of breast cancer, these data provide a rationale for targeting acetylated STAT3 for cancer therapy (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…5), thus providing new information on how U-STAT3 may contribute to the development of cardiac hypertrophy following angiotensin II stimulation. Additional Therapeutic Implications-Lee et al (25) reported that, by reducing STAT3 acetylation, ER␣ gene expression can be reactivated in tumors in which the ER␣ promoter had previously been methylated. Moreover, because inactivation of the ER␣ gene by DNA methylation strongly correlates with poor prognosis as well as an aggressive phenotype in cancers such as melanoma and the basal subtype of breast cancer, these data provide a rationale for targeting acetylated STAT3 for cancer therapy (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of this pathway resulted in tumor progression in preclinical studies (Carro et al, 2010). STAT3 induces methylation of the CDKN2A promoter which silences this important tumor suppressor (Lee et al, 2012). Activating tyrosine-protein phosphatase non-receptor type 11 (PTPN11) mutants inhibit STAT3 (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of acetylated form of STAT3 has been reported in case of melanoma, colorectal cancer, ovarian cancer [80], lung cancer as well as in case of triple negative breast cancer as compared to the adjacent normal tissue sample detected using immunohistochemistry [43]. The increased level of acetylated form of STAT3 promotes tumor growth in vivo while K685R mutant expressing cells showed significantly slower tumor growth.…”
Section: Ps727 Phosphorylation and K685 Acetylation Of Stat3: The Nonmentioning
confidence: 96%
“…In breast cancer patients, loss of SOCS3 expression was considered as a biomarker for poor prognosis and was shown to be associated with increased lymph node metastasis [42]. Recently it has been reported that the promoter of SOCS3 undergoes methylation at CpG island induced by AcK685 STAT3 and DNMT1 interaction in case of TNBC thereby promoting tumor growth [43].…”
Section: Socs3 Proteinsmentioning
confidence: 99%